Sol‐gel assisted synthesis of TiB2‐B4C composite powder. Issue 1 (13th September 2020) - GahremanDerakhshan, Mahnaz; Nikzad, Leila; Farvizi, Mohammad; Ebadzadeh, Touradj
Abstract: Composite powders containing titanium diboride and boron carbide have been prepared by sol‐gel method at 1450°C using titanium isopropoxide (titanium precursor), boric acid (Boron precursor), sucrose (carbon source), and acetic acid (AcOH) as a solvent. The effect of boron source (trimethyl borate and boric acid) and B2 O3 /TiO2, C/B2 O3 mole ratios of starting materials on the final phases has been studied. The progress of reactions was determined using thermal analysis (TGA‐DTA). The resultant powders were characterized by X‐ray diffraction (XRD) analysis and field‐emission scanning electron microscope (FESEM). XRD patterns confirmed the formation of TiB2, B4 C, and TiC phases after heat treatment at 1450°C at mole ratio of B2 O3 /TiO2  = 4.5, C/B2 O3  = 2.4. With increasing the content of boron oxide, the unwanted phases such as TiC and C were reduced. TiB2 and B4 C composite powders (~5 µm diameter) containing residual carbon (<4 wt%) were synthesized using the mole ratio of B2 O3 /TiO2  = 10 and C/B2 O3  = 1.9 at low temperature of 1450°C.